Teachers' and students' perceptions of ICT in english language learning at the primary level: A case study at SD Negeri 1 Suka Mukti - Permatasari, Gilang Lukito; Ariyani, Hastin Yoka; Firdaus, Masagus (Institute of Computer Science (IOCS), 2025)
This study investigates teachers’ and students’ perceptions of Information and Communication Technology (ICT) in English language learning at SD Negeri 1 Suka Mukti. The primary objective of this research is to explore how both teachers and students perceive the use of ICT in English learning and to identify the benefits and challenges they experience in its implementation. Using a mixed-methods approach that includes questionnaires, interviews, and classroom observations, the research examines perceived benefits, challenges, and the overall impact of ICT integration in the primary school context. The findings reveal that both teachers and students hold generally positive attitudes toward ICT. Students report increased motivation and engagement, while teachers highlight ICT’s ability to diversify instructional strategies and support individualized learning. Nevertheless, challenges persist, particularly in regard to limited infrastructure, varying digital literacy levels, and insufficient pedagogical training. These results suggest that effective ICT implementation requires not only technological resources but also teacher capacity-building and supportive institutional policies. Overall, the study underscores ICT’s transformative potential in enhancing English language teaching and learning in Indonesian primary schools.